Conceptual Metaphor Analysis in JVKE’s Song Golden Hour: A Cognitive Linguistics Approach - Trisnadi, Farhan Maulana; Djuharie, Otong Setiawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study investigates the metaphorical expressions in the song Golden Hour by JVKE using Conceptual Metaphor Theory (CMT) by Lakoff and Johnson (1980). The research aims to identify and analyze metaphors that represent emotional experiences, particularly romantic feelings, through the use of concrete and sensory imagery. Using a qualitative descriptive method, the lyrics of Golden Hour were analyzed to uncover how metaphorical language shapes the expression of love and emotional transitions. The findings reveal several dominant metaphor categories such as LOVE IS LIGHT, LOVE IS A JOURNEY, and EMOTION IS ELEVATION. These metaphors transform abstract emotions into vivid, relatable experiences by linking them to concepts like time, nature, and movement. The study concludes that metaphor in song lyrics functions as a cognitive and poetic device that enhances meaning and emotional resonance. The implications of this research highlight the relevance of metaphor analysis in understanding language, thought, and culture, especially in modern musical texts.